Kosovo : what everyone needs to know - Judah, Tim, 1962- (Oxford University Press, 2008)
C Preface: Why Kosovo?. Who are the Albanians?. Who are the Serbs?. Why is Kosovo so important to Serbs?. A Brief History. Kosovo in World War Two. Kosovo in Yugoslavia. The Beginning of the end. Who was Milosevic? How did he use Kosovo?. The birth of the Kosovo Liberation Army. The UN years. 1999 -?. Who wants what?. Kosovo and the Region. Kosovo and the World. Conclusion.